Estrogen‐related receptor γ is an in vivo receptor of bisphenol A. Issue 7 (17th April 2014) - Tohmé, Marie; Prud'homme, Sophie M.; Boulahtouf, Abdel; Samarut, Eric; Brunet, Frédéric; Bernard, Laure; Bourguet, William; Gibert, Yann; Balaguer, Patrick; Laudet, Vincent
ABSTRACT: Bisphenol A (BPA) is an endocrine disruptor that displays estrogenic activity. Several reports suggest that BPA may have estrogen receptor‐independent effects. In zebrafish, 50 μM BPA exposure induces otic vesicle abnormalities, including otolith aggregation. The purpose of this study was to test if BPA action was mediated in vivo during zebrafish development by the orphan nuclear estrogen related receptor (ERR) γ. Combining pharmacological and functional approaches, we demonstrate that the zebrafish ERRγ mediates BPA‐induced malformations in otoliths. Using different bisphenol derivatives, we show that different compounds can induce a similar otolith phenotype than BPA and that the binding affinity of these derivatives to the zebrafish ERRγ correlates with their ability to induce otolith malformations. Morpholino knockdown of ERRγ function suppresses the BPA effect on otoliths whereas overexpression of ERRγ led to a BPA‐like otolith phenotype. Moreover, a subphenotypical dose of BPA (1 μM) combined with ERRγ overexpression led to a full‐dose (50 μM) BPA otolith phenotype. We therefore conclude that ERRγ mediates the otic vesicle phenotype generated by BPA. Our results suggest that the range of pathways perturbed by this compound and its potential harmful effect are larger than expected.—Tohmé, M., Prud'homme, S. M., Boulahtouf, A., Samarut, E., Brunet, F., Bernard, L., Bourguet, W., Gibert, Y., Balaguer, P., Laudet, V. Estrogen‐related receptor γ is an in vivo receptor of bisphenol A. FASEB J . 28, 3124–3133 (2014). www.fasebj.org